Isolation and Some Basic Characteristics of Lactic Acid Bacteria from Honeybee (Apis mellifera L.) Environment—A Preliminary Study - Aleksandra Leska; Adriana Nowak; Ilona Motyl (Agriculture, 2022)
In light of the phenomenon of colony collapse disorder, there has been a growing interest in finding natural and ecological ways for improving honeybee health. The aim of this scientific research was the isolation and characterization of LAB, which in the future could show the potential to construct a protective preparation for honeybees. After performing MALDI-TOF analysis, of a total of 76 bacterial strains isolated from flowers and honeybee products, 31 were identified as Pediococcus pentosaceus, 26 as Pediococcus acidilactici, and 19 as Lactiplantibacillus plantarum. The characterization of the isolated LAB displayed that CO2 production was present in 52 strains. The highest biomass productivity was observed in the case of strain 9/1 isolated from red clover (Trifolium pratense L.) with biomass productivity equal to 2.100. All isolated bacterial strains showed the ability to produce lactic acid. The strain 13/3 isolated from small-leaved lime (Tilia cordata L.) displayed the highest lactic acid production capacity in 100 mL of culture, i.e., 1.903 g of lactic acid. The carbohydrate assimilation pattern was examined using API 50 CH tests. All isolated strains were able to utilize esculin, D-ribose, D-galactose, D-glucose D-fructose, and D-mannose. It was also noted that the reduction of sugars is a strain-dependent ability and is specific for individual strains.